UPAYA PEMBERDAYAAN PENGGUNAAN BAHASA DAERAH MELALUI BUDAYA LITERASI DIGITAL - Ratumanan, Stelie D; Rahman, H; Karlina, Dety Amelia; Rahayu, Galih Dani Septiyani; Anggraini, Gian Fitria (COLLASE (Creative of Learning Students Elementary Education), 2022)
An advanced society is always changing according to the development of a better life. They are always looking for new information so as not to be out of date so that they can compete with other communities. The widespread use of technology in the era of globalization is increasing day by day. Through the use of technology in the 4.0 era, anyone anywhere and anytime can access all the information that exists in any corner of the world. With the help of technology, all information can be accessed quickly, this of course provides convenience in all fields of work. One of the advantages of using information technology is capturing, processing, storing and retransmitting data needed by humans. There are two approaches that can be taken on digital literacy covering two aspects, namely conceptual and operational approaches. One example is as in the educational environment, information technology is used by students in learning activities through the use of computers in schools or colleges that are supported by internet technology. However, without realizing it, in the midst of incessant efforts to modernize themselves, the community is also required to always be aware of and preserve its cultural wealth, namely regional languages that have existed as intellectual property for a long time. This regional language is the result of the creativity of our ancestors in daily communication to deal with any situation. One of the efforts that can be done is through a digital literacy culture. Empowerment of the use of regional languages can be done by implementing digital literacy in families, schools and communities.